2014
DOI: 10.1144/jgs2014-055
|View full text |Cite
|
Sign up to set email alerts
|

The Fram Slide off Svalbard: a submarine landslide on a low-sedimentation-rate glacial continental margin

Abstract: Submarine slope failures are a widespread, hazardous phenomenon on continental margins. The prevailing opinion links large submarine landslides along the glaciated NW European continental margins to overpressure generated by the alternation of rapidly deposited glacigenic and hemipelagic material. Here, we report a newly discovered large landslide complex off NW Svalbard. It differs from all known large slides off NW Europe, as the available data rule out that this slope failure resulted from rapid glacigenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…There are not many submarine landslides known and studied in the European Arctic apart from the Hinlopen/Yermak slide complex (Winkelmann and Stein, 2007) and the Fram Slide (Elger et al, 2015). Elger et al (2015) reported on the extent of the Fram Slide and compared it with the typical characteristics of slope failures on the NE Atlantic glaciated margin. That study confirmed that submarine slope failure in the NE…”
Section: Introductionmentioning
confidence: 99%
“…There are not many submarine landslides known and studied in the European Arctic apart from the Hinlopen/Yermak slide complex (Winkelmann and Stein, 2007) and the Fram Slide (Elger et al, 2015). Elger et al (2015) reported on the extent of the Fram Slide and compared it with the typical characteristics of slope failures on the NE Atlantic glaciated margin. That study confirmed that submarine slope failure in the NE…”
Section: Introductionmentioning
confidence: 99%
“…SBF Sjubrebanken Fan Contourite-drift deposition dominated the overall sedimentary environment in the eastern Fram Strait since at least 11 Ma and numerous sediment drifts have been identified on the continental slope off western Svalbard, mainly at water depths exceeding 1200 m [7,21,23,24,41,57,61]. However, multiple escarpments north of the study area provide evidence of repeated downslope sediment transport ( [10,50]). …”
Section: Physiographymentioning
confidence: 99%
“…Multiple slide scars resulting from large-scale mass wasting occur below 1300-1400 m in the northern part of the study area (Figs. 3, 4e, 5; for details, see [10,50].…”
Section: Overall Bathymetrymentioning
confidence: 99%
“…Haflidason et al 2004;Baeten et al , 2014Elger et al 2015). Haflidason et al 2004;Baeten et al , 2014Elger et al 2015).…”
Section: Introductionunclassified
“…Slope failures occurred frequently during peak glaciation when grounded ice sheets extended to shelf break and the mouths of glacial shelf troughs (e.g. Baeten et al , 2014Elger et al 2015). However, the rapid deposition of glacigenic debris lobes on fine-grained contouritic deposits with high water content may lead to overpressure in the latter, facilitating the development of large-scale submarine landslides during interglacials (e.g.…”
Section: Introductionmentioning
confidence: 99%